2018
DOI: 10.1590/s0004-2803.201800000-15
|View full text |Cite
|
Sign up to set email alerts
|

Association of Potential Celiac Disease and Refractory Iron Deficiency Anemia in Children and Adolescents

Abstract: Frequency of potential celiac disease in patients with refractory IDA was higher than control the subjects. Therefore, we recommend serologic screening for early detection and minimizing the complications of celiac disease and repeated iron therapy for this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…A cross-sectional study on 290 patients (age more than 12 years) diagnosed with IDA showed that tTGs were found in 32 (11%) of these patients (p = 0.0002) [35]. Shahriari et al studied 184 children: 92 patients with IDA responsive to iron supplementation, 45 patients with IDA unresponsive to iron supplementation, and 47 controls [36]. They found that the frequency of positive antibodies for CD was higher in the second group compared with the other two groups (p < 0.001).…”
Section: Iron Deficiency Anemia and Relationship With Clinical And Himentioning
confidence: 99%
“…A cross-sectional study on 290 patients (age more than 12 years) diagnosed with IDA showed that tTGs were found in 32 (11%) of these patients (p = 0.0002) [35]. Shahriari et al studied 184 children: 92 patients with IDA responsive to iron supplementation, 45 patients with IDA unresponsive to iron supplementation, and 47 controls [36]. They found that the frequency of positive antibodies for CD was higher in the second group compared with the other two groups (p < 0.001).…”
Section: Iron Deficiency Anemia and Relationship With Clinical And Himentioning
confidence: 99%
“…Malabsorption causes should be considered especially in refractory IDA; this malabsorption can be the only manifestation in subclinical and silent CD [29,30]. The study of Shahriari et al [11] suggests serologic screening for CD in patients with refractory IDA to minimize the complications of CD and repeated iron treatment. A study [31] revealed a significant association between H. pylori infection and IDA in patients with CD, and Samasca et al [32] recommend performing the screening for H. pylori infection in patients with CD and ID, but currently there is no evidence to support this recommendation.…”
Section: Micronutrient Deficiencies and Celiac Diseasementioning
confidence: 99%
“…A recent meta-analysis found that more than 3% of patients with IDA have histological evidence of CD. This high percentage of subjects with IDA who are celiac, reinforces the need for screening CD in patients with IDA [11]. Folate and vitamin B 12 malabsorption, nutritional deficiencies, blood loss, inflammation, development of refractory CD or concomitant Helicobacter pylori infection are other causes of anemia in such patients [12] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, heme-iron is absorbed in the same bowel district, but separately from DMT1 and more efficiently than inorganic iron [1][2][3]. This portion of the duodenum represents the most frequently destroyed region in CD, consequently resulting in a reduction in iron absorption, and therefore IDA, which is another of the most frequent extra-intestinal manifestations (EIM) of CD [5][6][7][8][9][10][11][12]. The prevalence of anemia, different due to the high variability of the studies on this topic, is estimated at between 12 and 82% in patients with new CD diagnosis and about 46% in patients affected by subclinical CD [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Shahriari et al studied the prevalence of IDA in 184 children (92 patients with IDA responsive to iron supplementation, 45 patients with IDA unresponsive to iron supplementation). The authors showed a positive serology of CD in 5.4% and in 28.3% of children with responsive and refractory IDA, respectively [ 5 ]. Ertekin et al reported that among 61 children with IDA, 21.3% had positive serology for CD [ 28 ] and Karaman et al found positive serology for CD in about 8.4% of 250 children with IDA [ 29 ].…”
Section: Introductionmentioning
confidence: 99%